A Survey on Ethnic Foods and Desserts of Mohr City in Fars - Parmis Badr; Sedigheh Khademian (Tehran University of Medical Sciences, 2019)
Ethnic foods, a distinctive part of a cultural group or nation, have recently attracted scientists' attention because of their potential health benefits. The city of Mohr in Fars province has an old record in history, dating back to periods of Achaemenids and Sasanids. To collect local data about ethnic foods and desserts of Mohr city, a questionnaire was designed and handed out to students of one high school. Thirty female students, familiar with the city culture and rituals, answered the questionnaire. The average age of respondents was 16.04 ± 0.84 years. The references were women in the families, mostly mothers. Thirteen desserts and fourteen types of food were extracted from questionnaires. Among local foods, Sorou, Sholak, Reshtakou, and Gevzeh were highly mentioned. Halva Khorma, Ranginak, Jollab, Kaster, and Dishou had higher numbers among Mohr ethnic desserts. Using local products like date, fish, and wheat as food ingredients was more common. Recording old recipes and eating behaviors of ethnic groups are of great importance. For the next step, health benefits of these dishes are suggested to be deeply studied in further research.